Wisdom from Arabian Creatives: Systematic Review of Innovation Management Literature for the Gulf Cooperation Council (GCC) Region - Durugbo, Christopher M.; Al-Jayyousi, Odeh R.; Almahamid, Soud M. (International journal of innovation and technology management, 2020)
Innovation management (IM) for the Gulf Cooperation Council (GCC) region poses unique socio-economic challenges due to the multi-faceted nature of Arab and Islamic countries. Additionally, proposals for indigenous initiatives, sustainability transitions and outward-oriented strategies in economic reform plans of the GCC add further complexity to IM scholarship and practice with imperatives to harness the potentials of these strategic visions. Yet, there is an absence of a systematic review to scrutinize IM literature on the GCC region. This paper systematically reviews the IM literature whose subject involve the GCC countries of Bahrain, Kuwait, Oman, Qatar, the United Arab Emirates and Saudi Arabia. The review scrutinizes theories, trends and targets in this literature, covers the period from 1980 to 2019, and involves 110 journal papers from high quality IM-related publication outlets. Using insights from the review, the paper develops theoretical foundations for creative complementarities, institutional-pumps and a ripple model of regional innovation. The review also details some methodological, theoretical, conceptual and topical directions for future regional IM research studies.